Surface interaction between carbon patches and catalyst nanoparticle as the key factor in aligned carbon nanotube growth using alcohol catalytic CVD - Bistamam, Mohd Shahril Amin; Mohd Abid, Mohd Asyadi Azam; Zulkapli, Nor Najihah (World Scientific Publishing Company, 2017)
Aligned carbon nanotubes (ACNTs) have very unique properties that made them applicable as electrode material for energy storage devices. ACNTs were grown directly on substrates by catalytic chemical vapor deposition (CVD). Cobalt, thermally-oxidized aluminum and ethanol were used as catalyst, catalyst-support and carbon feedstock, respectively. Optimum catalytic and reaction conditions were investigated by varying the CVD processing temperature and time. CVD processing temperature of 725C and processing time at 10 min showed the optimum CNT alignment with thickness of above 2 m. Other than the e®ect of catalyst particle diameter, formation of amorphous carbon at the top of CNTs observed by SEM is suggested as another factor that in°uences the growth mechanism of ACNTs. The CVD processing parameter and the interaction between small carbon patches are supposed to be built after dehydrogenation of the¯rst carbonaceous molecules and the catalyst nanoparticle surface considered as the hidden factors behind the growth results